ANALYSING STUDENT MENTAL HEALTH THROUGH K-MEANS CLUSTERING AND MULTI-STAGE SAMPLING METHODS - Rahmat Hidayat; Dede Pratama (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: Mental health is an essential aspect of overall well-being, particularly for university students vulnerable to emotional strain. This study aims to identify clusters of student mental health trends using the K-Means clustering technique. The research involved 60 students from four academic programs at the Faculty of Science and Technology, selected using stratified and cluster sampling techniques. Data were collected using a modified Mental Health Inventory (MHI). The results revealed distinct commonalities among majors: the Statistics program was predominantly defined by the depressed cluster at 53.3%, while Mathematics followed at 40% within the same cluster. In contrast, Biology students predominantly fell under the neu-tral/stable cluster (66.7%), whilst Information Systems students exhibited an even distribution (33.3% per cluster) without a dominant trend. The clustering quality was evaluated using the Silhouette Coefficient, yielding a range of 0.39 to 0.60. Biology (0.60) and Statistics (0.54) exhibited a reasonable structure, but Information Systems (0.39) and Mathematics (0.34) demonstrated a deficient structure. In conclusion, K-Means effectively discerns mental health patterns, providing a data-driven basis for targeted psychological interventions in educational settings. Keywords: biology; information systems; k-means; mathematics; mental health; silhouette coefficient; statistics Abstrak: Kesehatan mental merupakan komponen vital dari kesejahteraan total, terutama bagi maha-siswa yang rentan terhadap stres emosional. Penelitian ini bertujuan untuk mengidentifikasi kelompok tren kesehatan mental mahasiswa melalui penerapan metode pengelompokan K-Means. Studi ini mencakup 60 mahasiswa dari empat program studi di Fakultas Sains dan Teknologi, yang dipilih melalui metode pengambilan sampel bertingkat dan kelompok. Data dikumpulkan dengan menggunakan Inventaris Kesehatan Mental (MHI) yang dimodifikasi. Temuan menunjukkan kesamaan yang jelas di antara jurusan: program studi Statistika terutama ditandai oleh kelompok depresi (53,3%), diikuti oleh Matematika dengan 40% dalam kelompok depresi. Sebaliknya, mahasiswa Biologi terutama termasuk dalam kelompok netral/stabil (66,7%), sedangkan mahasiswa Sistem Informasi memiliki distribusi yang merata (33,3% per kelompok) tanpa pola yang dominan. Kualitas pengelompokan dinilai dengan Koefisien Sil-houette, menghasilkan rentang 0,39 hingga 0,60. Biologi (0,60) dan Statistika (0,54) memiliki struktur sedang, sedangkan Sistem Informasi (0,39) dan Matematika (0,34) menunjukkan struktur yang buruk. Kesimpulannya, K-Means secara akurat mengidentifikasi tren kesehatan mental, menawarkan landasan berbasis data untuk terapi psikologis yang ditargetkan di ling-kungan pendidikan. Kata kunci: biologi; kesehatan mental; K-Means; matematika; silhouette coefficient; sistem in-formasi; statistika